Entre a singularidade e a complexidade da construção de saberes docentes na formação Inicial de professores de matemática no contexto do Pibid - Abreu, Iury Sparctton Melchior de (2016)
The goal of this work, whose central theme evidences the training of mathematics teachers, is to understand the influence of the environment provided by the Institutional Program Initiation of Scholarships for Initiation in Teaching - Pibid for the construction of the essential knowledge for initial teacher training. As it is the study of a specific group, in an institution of higher education, this research is characterized as a quali-quantitative case study, with the dialectical historical materialism method, which seeks to establish the relationship between the singularity and the complexity of teacher training in the Pibid. We addressed several aspects of the theme: History of teacher training in Brazil; National Education Guidelines and Framework Law; Teacher training in Federal institutes; Curriculum and profile of the student of the Teaching Degree in Mathematics; Essential knowledge for teacher training and the influence of Pibid in the construction of knowledge. The theoretical framework that supported these discussions consisted of contributions from various national and international researchers, in addition to official documents that structure and standardize the Brazilian education and Pibid. From literature in Education: Libâneo (1992); Nóvoa et al. (1995); Freire (1996); Alarcão (1996); Pimenta (1996); Masetto (1998); Demo (2006); Gatti (2008); Saviani (2009); Frigotto (2011). From literature specific to Mathematics education: Fiorentini and Miorim (1990); Grando (2000). From literature relative to Pibid: André (2012); Fetzner and Souza (2012); Jardilino and Oliveri (2014). From official documents: Law 9394/96 – LDB; Law 11892, of December 29th, 2008; Ordinance 096, of July 18th, 2013. Empirical data were obtained by direct observation of the researcher in the research environment and semistructured questionnaires, answered by the scholarship students of the subproject PibidMathematics of the Federal Institute of the state of Goiás, Campus Urutaí. The categories used for data analysis were: Knowledge of the Specific Scientific Field, Knowledge of the Pedagogical-Didactic Field, Knowledge of the Experiential Field and Knowledge of the Political Field. These categories were constructed through the analysis of initial teacher training and an intensive and delicate examination of the questionnaires, using data triangulation as the analysis technique. The data obtained showed elements which enabled the analysis of some aspects of initial teacher training, specifically those related to the construction of teaching knowledge. We understand the Pibid as a program that contributes greatly to the development of the Knowledge of the Specific Scientific Field, Knowledge of the Pedagogical-Didactic Field, Knowledge of the Political Field and Knowledge of the Experiential Field. Furthermore, we found that the relationship between the theory of Higher Education and professional practice in Basic Education contributes to both the initial training of scholarship students, and for the continuing education of supervisor teachers of Pibid. This training occurs by means of exchange of knowledge and experience of both, teamwork, suggestions, teaching practices and methodologies proposed by the group.